NAHosMIP data ... - Jackson, Laura; Alastue de Asenjo, Eduardo; Bellomo, Katinka; Danabasoglu, Gokhan; Hu, Aixue; Jungclaus, Johann; Lee, Warren; Meccia, Virna; Saenko, Oleg; Shao, Andrew; Swingedouw, Didier (Zenodo, 2023)
This package is of data and code from the publication Jackson et al, (2022), Understanding AMOC stability: the North Atlantic Hosing Model Intercomparison Project. GMD [Full reference to come] This is the initial paper of the North Atlantic Hosing Model Intercomparison Project (NAHosMIP). See https://www.tipes.dk/na-hosing-mip/ Data included is from several experiments: Priority u03-hos Uniform hosing of 0.3Sv in the North Atlantic Priority u03-r20 Initialised 20yrs into u03-hos with no additional hosing Priority u03-r50 Initialised 50yrs into u03-hos with no additional hosing u03-r70 Initialised 70yrs into u03-hos with no additional hosing u03-r100 Initialised 100yrs into u03-hos with no additional hosing Priority g01-hos Hosing around Greenland of 0.1Sv Priority g01-r50 Initialised 50yrs into g01-hos with no additional hosing g01-r100 Initialised 100yrs into g01-hos with no additional hosing The models that have run this protocol are: CESM2, CanESM5, EC-Earth3, HadGEM3-GC3-1LL, HadGEM3-GC3-1MM, ...